ON THE ISSUE OF INVESTMENT ACTIVITY OF BANKS IN RUSSIA - NIKULINA S.A. (Legal Bulletin)
The article deals with the investment activities of banks, in particular commercial ones. The relevance of this topic is determined by the increased demand for the possibility of obtaining passive income, which is interesting for both ordinary citizens and banks. And despite the fact that investment activity is a rather new concept, which is still not sufficiently understood by many people, the active development of this institution is already observed, there are certain results both from commercial banks and from individuals carrying out investment activities with the help of banks. The main purpose of the work is to identify the problems of investment activities of commercial banks and offer possible solutions. The problems under consideration. The article discusses two possible options for the investment activities of banks: when they invest with the help of banks and they, in turn, act as intermediaries, and when the banks themselves invest directly. Legal problems are highlighted, as well as economic, as well as some organizational ones that one has to face in the practice of implementing the investment activity itself. The methods used. In addition to using general scientific research methods, special legal and economic methods will also be applied.